The Traditional Way of Thinking of Small Farmer Housewives in Finland - Halmesvirta, Anssi (Ethnographica et Folkloristica Carpathica, 2025)
The aim of this article is to throw light on the historical experiences and their memories of a housewife from a small farm in Upper Savo (Yläsavo) in Finland. Its motivation emanates from the fact that neither local, commissioned histories nor ethnographical studies have touched the orbit of their lives and their traditional, three-dimensional way of thought. The theoretical vantage-point applied here was put forward by Paul Ricoeur and further developed by Frank Ankersmit: memories of witnesses of historical experiences can tell more intimate and accurate narratives than documentary histories. As evidence, culled from interviews and diverse biographical and autobiographical material, they can complement the work of ethnographers who operate on the same field by recording past as lived life.